2011
DOI: 10.1186/1752-1947-5-203
|View full text |Cite
|
Sign up to set email alerts
|

A sleeping phantom leg awakened following hemicolectomy, thrombosis, and chemotherapy: a case report

Abstract: IntroductionWe describe the case of a patient who experienced phantom pain that began 42 years after right above-the-knee amputation. Immediately prior to phantom pain onset, this long-term amputee had experienced, in rapid succession, cancer, hemicolectomy, chemotherapy, and thrombotic occlusion. Very little has been published to date on the association between chemotherapy and exacerbation of neuropathic pain in amputees, let alone the phenomenon of bringing about pain in amputees who have been pain-free for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…1,2 As about 50% of patients with PLP report daily pain, PLP significantly worsens their quality of life (QoL). 3 Reviewers have concluded that PLP is extremely difficult to treat, 4 and common pain treatment is rarely effective. 2 Military conflicts; and road, extreme-sport, and other accidents, for instance, are the main reasons for an increased number of wounded patients with single-and multiple-limb amputations.…”
mentioning
confidence: 99%
“…1,2 As about 50% of patients with PLP report daily pain, PLP significantly worsens their quality of life (QoL). 3 Reviewers have concluded that PLP is extremely difficult to treat, 4 and common pain treatment is rarely effective. 2 Military conflicts; and road, extreme-sport, and other accidents, for instance, are the main reasons for an increased number of wounded patients with single-and multiple-limb amputations.…”
mentioning
confidence: 99%